Predictors of aneurysm shrinkage after flow diversion treatment for internal carotid artery aneurysms: quantitative volume analysis with MRI - Akiyama, Ryo; Ishii, Akira; Kikuchi, Takayuki; Okawa, Masakazu; Yamao, Yukihiro; Abekura, Yu; Ono, Isao; Sasaki, Natsuhi; Tsuji, Hirofumi; Matsukawa, So; Miyamoto, Susumu (Frontiers in Neurology, 2023)
Background and purpose Although aneurysm shrinkage often occurs after flow diversion treatment for intracranial aneurysms, no reports have addressed the factors associated with aneurysm shrinkage. Materials and methods This retrospective single-center study was performed to examine patients with unruptured internal carotid artery aneurysms who were treated using flow diversion and followed up by imaging for at least 12 months. The study outcome was aneurysm shrinkage (volume reduction of ≥10%) 12 months after treatment. Aneurysm volume was quantitatively assessed using the MRIcroGL software. Patient and aneurysm characteristics were statistically analyzed. Results This study involved 81 patients with 88 aneurysms. At the 6 months, 12 months, and last follow-ups, the proportion of aneurysms that had shrunk was 50, 64, and 65%, respectively. No adjunctive coiling (odds ratio, 56.7; 95% confidence interval, 7.03–457.21; p < 0.001) and aneurysm occlusion (odds ratio, 90.7; 95% confidence interval, 8.32–988.66; p < 0.001) were significantly associated with aneurysm shrinkage. In patients treated by flow diversion with adjunctive coiling, only the volume embolization rate was a factor significantly associated with aneurysm shrinkage (p < 0.001). Its cutoff value was 15.5% according to the receiver operating characteristic curve analysis (area under the curve, 0.87; sensitivity, 0.87; specificity, 0.83). Conclusion The rate of aneurysm shrinkage after flow diversion increased during the first 12 months after treatment, but not thereafter. No adjunctive coiling and aneurysm occlusion were predictors of aneurysm shrinkage, respectively. If adjunctive coiling is required, a volume embolization rate of ≤15.5% may be suggested for aneurysm regression.